Drag coefficient of circular cylinder in axial flow of water for a wide range of length to diameter ratios. Issue 12 (2nd December 2022) - Iiyama, Tsugumasa; Furuya, Masahiro; Arai, Takahiro; Ui, Atsushi; Okawa, Riichiro; Shirakawa, Kenetsu; Shimada, Taro
ABSTRACT: An experimental campaign was conducted to determine drag coefficients of circular cylinders in axial flow of water for a wide range of length-to-diameter ratios ( L/D ) from 2 to 35. Drag force acting on the circular cylinders was acquired at a velocity of 2 to 6 m/s, which corresponds to the Reynolds numbers of 2.2 × 10 5 to 7.0 × 10 5 . The experimental data were validated by analysis using the commercial CFD code, Star-CCM+. The measured drag coefficients increased monotonically as the L/D increased with the range of Reynolds numbers, and were almost constant regardless of the Reynolds number. The drag coefficient was decomposed by the term of form drag and skin friction. As the value of L/D increased, the drag coefficient increased due to the skin friction drag term. The drag coefficient correlation was proposed as a function of L/D . The predicted values were consistent with both the experimental data and numerical simulation results. Furthermore, this correlation was applied to a fuel assembly with a channel box, it was shown that the drag coefficient can be predicted for a wide range of Reynolds numbers by specifying an appropriate form drag term.